1992
DOI: 10.1007/bf00019206
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a chimaeric heat-shock-inducible Agrobacterium 6b oncogene in Nicotiana rustica

Abstract: The T-6b gene of Agrobacterium tumefaciens strain Tm4 induces tumours on Nicotiana rustica by an as yet unknown mechanism. These tumours cannot be regenerated into normal plants. To study the effect of the T-6b gene product on normal plant cells, the T-6b gene was placed under control of the Drosophila melanogaster hsp70 heat-shock promoter and introduced into N. rustica. Progeny of an hsp70-T-6b transformant developed into normal plants. The inducibility of the hsp70-T-6b construct was shown by northern analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 32 publications
3
33
0
1
Order By: Relevance
“…Two other T-DNA genes are thought to play ancillary roles in tumorigenesis. The gene 5 product directs the synthesis of indole-3-lactate, an antagonistic auxin analogue (57), while tml (also designated gene 6b) increases the sensitivity of plant cells to phytohormones by a mechanism that remains to be discovered (108). This gene can provoke tumors in certain host plants in the absence of the other oncogenes (42).…”
Section: Expression and Functions Of Transferred Genesmentioning
confidence: 99%
“…Two other T-DNA genes are thought to play ancillary roles in tumorigenesis. The gene 5 product directs the synthesis of indole-3-lactate, an antagonistic auxin analogue (57), while tml (also designated gene 6b) increases the sensitivity of plant cells to phytohormones by a mechanism that remains to be discovered (108). This gene can provoke tumors in certain host plants in the absence of the other oncogenes (42).…”
Section: Expression and Functions Of Transferred Genesmentioning
confidence: 99%
“…Various phenotypic effects associated with the expression of 6b have been reported, as follows: (1) formation of tumors on certain plants (Hooykaas et al, 1988;Spanier et al, 1989;Tinland et al, 1989Tinland et al, , 1992; (2) stimulation of the ipt -induced and iaaM / iaaH -induced division of cells (Tinland et al, 1989(Tinland et al, , 1990Wabiko and Minemura, 1996); (3) reduction in the formation of shoots on leaf discs that is normally induced by appropriate levels of exogenous or endogenous cytokinin (Spanier et al, 1989); (4) generation of shoot-bearing calli on leaf discs on phytohormone-free medium (Wabiko and Minemura, 1996); (5) inhibition of the growth of Rol -induced hairy roots via the induction of an undifferentiated state and the formation of calli (Tinland et al, 1990); and (6) alterations in the morphology of leaves of transgenic tobacco plants that express the 6b gene (Tinland et al, 1992;Wabiko and Minemura, 1996). Although there are some discrepancies among previously reported results (Leemans et al, 1982;Ream et al, 1983), it is accepted generally that the product of 6b stimulates the proliferation of plant cells and affects the development of 1 Current address: National Institute for Basic Biology, 38 Nishigounaka, Myo-daiji-cho, Okazaki 444-8585, Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, when we consider the possible mechanisms of action of the 6b protein in plant cells, we must remember that, in chimeric plants that were generated by grafting the stem of a 6b -transformed plant onto that of a normal plant, the effect of 6b was found only in the 6b -transformed portion. Thus, the product of the 6b gene appears to be nondiffusible (Tinland et al, 1992). This conclusion is consistent with the hypothesis that the levels of cytokinin and auxin, which basically are diffusible within a plant, are not affected by expression of the 6b gene (Wabiko and Minemura, 1996).…”
mentioning
confidence: 99%
“…In addition to these genes, a gene designated 6b, which is localized at the tml locus (Garfinkel et al, 1981;Willmitzer et al, 1983) and has been found in the T-DNA of all strains of A. tumefaciens and Agrobacterium vitis examined to date (Otten and De Ruffray, 1994), appears to play a role in the proliferation of plant cells. This gene modifies the morphology of crown galls but is not required for their formation (Garfinkel et al, 1981;Tinland et al, 1992), and it induces callus formation on tobacco (Nicotiana tabacum) leaf discs in the absence of exogenous auxin and cytokinin (Wabiko and Minemura, 1996;Kitakura et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Various hypotheses have been proposed to explain the effects of 6b on the growth of plant cells (Leemans et al, 1982;Ream et al, 1983;Hooykaas et al, 1988;Tinland et al, 1992;Wabiko and Minemura, 1996). This gene modulates the inductive effects of cytokinins on shoot development (Spanier et al, 1989); it interferes with the induction and elongation of roots in an auxindependent rolABC-based rooting assay, suggesting that 6b might reduce the effect of high levels of auxin to maintain cells in an undifferentiated state (Tinland et al, 1990); and it enhances the effects of both auxin and cytokinin on crown gall formation (Canaday et al, 1992).…”
Section: Introductionmentioning
confidence: 99%